Pengaruh Media Online terhadap Minat Belajar Siswa: Studi Kasus: SMK Islam Wijaya Kusuma - Aji Darusman (LITERATUS, 2019)
This research aimed to know how big the influence of online media on student interest in learning at wijaya kusuma islamic vocational high school. The research method used is quantitative method, field research method and library method . Population in this research is the students at Wijaya Kusuma Islamic Vocational School with a total of around 500 students with a sample of 50 respondents. This research using a quesionere instruments To test data analysis using method of Product Moment Correlation, Coefficient of Determination and Hypothesis test. Conclusion gwhich have been obtained after research that regression analysis Y = 47,66 + 0,55x and correlation analysis equal to r =0,573 which means a moderate influence between online media with student interest in learning. While result of Coefficient Determination analysis show equal to 32,8% the variable x (online media) contributes to the variable y (student intereset in learning) and the remaining as much 67,2% is determined by others variable. The last result hypothesist test showing a strong effect between variable x (online media) to variable y (student intereset in learning) ) at 5% significant level (? = 0,05 t count is bigger than t table.(5,90625>1,67722))